ANALISIS LAJU KOROSIF FLUIDA CAMPURAN REFINERY BLEACHING DEODORIZE PALM (RBDP) OLEIN DAN ETHYLENE GLYCOL (EG) PADA BAHAN METAL - Istianto Budhi Rahardja; Azhar Basyir Rantawi; Hendra Saputra; Dian Oktavia Pambudi (Jurnal Teknologi, 2023)
Corrosion to metal materials contaminated by liquid fluids is strictly avoided and maintained, which will result in damage and erosion of the material. Metal materials are very easy to corrosion when contaminated with fluids. The fluid mixture given is RBDP Olein from refined palm oil (CPO) and EG. The research method used was experimental, in which metal objects were immersed in the RBDP Olein & EG fluid mixture for a certain time (Â± 3 months), by weighing the mass before and after immersion in the fluid mixture. The results of the mass weighing test obtained that the reduction was not significant at all, namely: 0.01 gr (0.25%) for Â± 3 months from the initial mass of the object with a corrosion rate value of 1.25605E-07 mm/y , as well as on the microstructure test of the object the workpiece has no defects, scale, or erosion that occurs on the workpiece, so that the workpiece does not a corrosive rate in the RBDP Olein & EG fluid.